Do performance approach‐oriented individuals generate creative ideas? The roles of outcome instrumentality and task persistence. Issue 3 (4th January 2018) - Li, Hua; Li, Fuli; Chen, Tingting
Abstract: The literature is inconclusive about the positive and negative effects of performance approach goal orientation (PAGO) (i.e., a focus on demonstrating high performance and outperforming others) on creativity. To address this issue, this study examines when and how PAGO stimulates or hinders employee creativity. Drawing on trait activation theory and a self‐regulatory perspective, we propose that outcome instrumentality (i.e., the perception that one will receive desired organizational outcomes when performing well) moderates the effects of PAGO on task persistence bidirectionally, which, in turn, facilitates or hinders employee creativity. Results based on a two‐wave, multi‐source field survey provided strong support for our hypotheses. We found that the relationship between PAGO and task persistence was positive when outcome instrumentality was high but became negative when outcome instrumentality was low. Moreover, we found a moderated mediation effect, such that the indirect effect of PAGO on creativity through task persistence was positive when outcome instrumentality was high but negative when outcome instrumentality was low. These findings extend the PAGO literature by elucidating the goodness and badness of PAGO and provide practical implications on how to manage performance approach‐oriented employees to capitalize on their creative potentials and minimize the possible detrimental effects of PAGO on creativity.